The transformative impact of advanced technologies blockchain, artificial intelligence (AI), and big data analytics on auditing profession - Ratna Sari; Muslim Muslim; Dian Indriani (Bata Ilyas Educational Management Review, 2024)
This study explores the transformative impact of advanced technologies—blockchain, artificial intelligence (AI), and big data analytics—on the auditing profession, examining their benefits, challenges, and implications for auditing standards and practices. A mixed-methods approach was adopted, combining quantitative surveys and qualitative interviews with audit professionals to gather comprehensive data on the integration and impact of these technologies in auditing. The findings reveal that blockchain enhances transparency and security, AI improves data analysis accuracy and risk assessment, and big data analytics provides deeper operational insights. However, these technologies also present challenges, including ethical concerns, the need for robust governance frameworks, and significant changes to workflows and skill requirements. Updated auditing standards and regulatory frameworks are crucial for effective technology integration. The study suggests actionable strategies for auditing firms to invest in advanced technologies, train auditors, and develop governance frameworks. These advancements can significantly enhance audit quality and reliability, shaping the future of auditing in an increasingly digital environment.